Investigation on dielectric properties and microwave heating efficiencies of various concrete pavements during microwave deicing. (20th November 2019) - Liu, Jun-liang; Xu, Jin-yu; Lu, Song; Chen, Haowen
Highlights: Open environment microwave machine was used to test pavement concrete during microwave deicing. Pavement concrete with different water cement ratio and sand ratio were prepared. Dielectric property of various mix concrete and graphite modified concrete are studied. Development prospect of microwave deicing technology is di technology is discussed. Abstract: The dielectric properties of pavement materials have a significant impact on microwave deicing efficiency. Moreover, the mix properties of pavement also significantly influence the dielectric properties. In this study, water/cement ratio, sand ratio, and addition of graphite were set as variables to form pavements with different mix properties. Subsequently, the dielectric abilities, microwave deicing efficiency, and static mechanical properties of the specimens were experimentally investigated. The results indicated that the real part of the complex dielectric constant of ordinary concrete remained in the interval between 6.69 and 7.76, while the imaginary part remained in the interval between 0.31 and 1.09; the loss tangent was in the low range from 0.04 to 0.15. The dielectric properties increased with both the water/cement ratio and the sand ratio, which enhanced the complex dielectric constant and microwave deicing efficiency of the pavement. Graphite-modified concrete (GC), which is more efficient in microwave deicing, was prepared by adding graphite as a wave-absorbing material to addition ratios of 5%, 10%, and 15%. The addition of graphite led to an evident increase in the complex dielectric constant and microwave deicing efficiency of the GC. The cost time for deicing of GC-3 was reduced to 90 s in comparison with that of PC. Additionally, changes in the basic mix proportion also decreased the static mechanical properties of the concrete. The variation of both the water/cement and sand ratios had a similar degree of influence—within 5%–10%—on the concrete strength and dielectric property. In comparison, the influence of graphite was in the high range from 149% to 254%. The addition of microwave-absorbing materials had a more evident influence than changing the basic mix proportions of the concrete.